Corporate board leadership and earnings informativeness - CHIRAPHOL, Chiyachantana N. (Institutional Knowledge at Singapore Management University, 2021)
This study examines the relationship between six board compositions and the informativeness of earnings. The results show that smaller board sizes are more informativeness of earnings. Longer board service time is viewed as the experience and expertise to manage the firms and increases informativeness of earnings. The average board tenure is positively significant with the informativeness of earnings. The accounting earnings generated from the firms with more independent directors and female directors are highly valued by the investors. Consequently, the accounting earnings generated from these firms are highly valuable to the investors.